The Relationship Between The Knowledge Of Pregnant Women About Section Caesarea And Anxiety In Pre Operative Patients In The Ikr Room On Hospital Dr. M. Ashari Pemalang District - anik Indriono; Kumaedi Kumaedi (Pena Medika Jurnal Kesehatan, 2019)
ABSTRACTIntroduction : Sectio caesarea is generally done when the vaginal delivery is not possible or because of medical or non-medical indications. Medical action is only carried out if there is a problem in the birth process that can threaten the life of the mother and fetus such as pregnancy with preeclampsia. Labor with Sectio caesarea surgery is a medical intervention that might cause an unexpected emotional reaction.Method: The design of this study was a descriptive correlational study with a cross sectional approach. The sample in this study was taken from all patients who will undergo labor with a Sectio Caesarea surgery procedure in the IKR Room of the RSUD Dr. M. Ashari Pemalang District. Sampling using accidental sampling method as many as 30 respondents. Statistical testing with chi-square correlation analysis.Results: The results showed that the majority of respondents had sufficient knowledge about the caesarean section at 73.3% and only 3.3% experienced severe anxiety levels. Chi-square  test result obtained p-value 0,825 > 0,05 with means H0 accepted.Conclusions: There is a no significant relationship between the knowledge of pregnant women about Section Caesarea and anxiety in preoperative patients in the IKR Hospital Dr. M. Ashari Pemalang District.Keywords: Preoperative knowledge, caesarean section, Anxiety